The Community as Sacrament - Liderbach, Daniel (Philosophy & theology, 1991)
I argue that the late twentieth century relies more upon the symbolic than upon the causal power of events acknowledged as sacraments. Since this is the case with the Eucharist no less than with other sacraments, the symbolic meaning of the Eucharist must be refocused. This may be accomplished through the concept of the numinous dimension of the Lord’s Supper.